2004
DOI: 10.3354/meps281121
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of movement of the limpet Cellana tramoserica on rocky shores and retaining seawalls

Abstract: Artificial structures are becoming common features of the landscape in shallow waters of urban areas, but very little is known about their ecology. In Sydney Harbour (NSW, Australia), intertidal seawalls replace considerable portions of natural habitats, including rocky shores. Previous studies have shown that seawalls and rocky shores generally support similar assemblages of plants and animals, with important differences in relative abundances of some species. The behaviour of key consumers can have a fundame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 66 publications
(97 reference statements)
0
12
2
Order By: Relevance
“…Manipulative experiments would be needed to establish whether individuals are active selecting steeply sloped microhabitats or if other processes are driving this pattern. Homing is unlikely to explain this pattern as previous studies have found only 10-15 % of Cellana home after 14 days on vertical surfaces (Bulleri et al 2004) compared to the 62 % of individuals consistently being found on steeply sloped surfaces in this study. Consistently being located on steeply sloped substrata is not associated with an increased chance of orientating downwards.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Manipulative experiments would be needed to establish whether individuals are active selecting steeply sloped microhabitats or if other processes are driving this pattern. Homing is unlikely to explain this pattern as previous studies have found only 10-15 % of Cellana home after 14 days on vertical surfaces (Bulleri et al 2004) compared to the 62 % of individuals consistently being found on steeply sloped surfaces in this study. Consistently being located on steeply sloped substrata is not associated with an increased chance of orientating downwards.…”
Section: Discussioncontrasting
confidence: 81%
“…The behaviour of intertidal animals on steeply sloped substrata has been relatively understudied compared with that of organisms on horizontal substrata and within specific microhabitats (see Della Santina 1994;Della Santina et al 1995;Chelazzi et al 1998;Bulleri et al 2004 for some exceptions). Global sea levels are predicted to rise as a result of climate change (Pachauri and Reisinger 2007), and consequently, the intertidal region may shift in many areas from predominately horizontal surfaces to increasingly dominated by steeply sloped and vertical surfaces (Vaselli et al 2008;Jackson and McIlvenny 2011), and the abundance of different habitat types will change (Thorner et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Alternatively, they may migrate into shaded patches only when temperatures are very hot and move back onto the unshaded wall when conditions are more benign. Whether the observed difference between shaded and unshaded portions of seawalls may be explained by behavioural responses to habitat differences cannot be tested here because there are few data on patterns of movement of mobile animals on intertidal seawalls (Bulleri et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Despite many papers in recent years documenting patterns of assemblages on seawalls, few have compared ecological interactions among animals between artificial and natural shores. Bulleri et al (2004) showed grazing by Cellana tramoserica on walls differed from that on natural shores in NSW, which could have major impacts on assemblages because of its strong interactions with other species (Underwood et al 1983, Underwood 1984. Intertidal shores in NSW are generally extensive wave-cut platforms, so interactions among grazers might be expected to be stronger on seawalls where the intertidal area is reduced and species are crowded into a limited area.…”
Section: Discussionmentioning
confidence: 99%